The longitudinal influence of hedonic and eudaimonic entertainment preferences on psychological resilience and wellbeing - Reinecke, Leonard; Kreling, Rebekka Johanna (Frontiers in Communication, 2022)
Narratives and media entertainment are central sources of meaningful experiences in everyday life and provide role models and learning opportunities for coping with adversity and life challenges. Though a growing body of research demonstrates beneficial short-term effects of entertainment use on recovery and stress coping, a test of longitudinal effects on positive adaptation to adversity is largely missing. The present study aims at providing a salutogenic perspective on the mental health effects of entertainment use by addressing the longitudinal relationship between hedonic and eudaimonic entertainment preferences (i.e., the individual entertainment diet) and three indicators of psychological resilience: hope, meaning in life, and trait resilience. Preregistered hypotheses and research questions were tested based on data from a longitudinal panel study with two waves over a six-month time period and N = 2,561 participants from Germany. The findings demonstrate that only meaning in life at T2 was significantly albeit weakly predicted by eudaimonic entertainment preferences at T1, providing limited support for prospective effects of entertainment use on resilience. In contrast, the data demonstrate selective exposure effects of hope and trait resilience at T1 on eudaimonic and hedonic entertainment preferences at T2. All three resilience indicators were significant predictors of mental health and psychological well-being. We discuss implications of our findings for future research on salutary mental health effects of narratives and media entertainment.